Definition of the operating mode of ejection flotator for the wastewater treatment - Ekaterina S. Antonova; Veronika O. Karpikova (RUDN Journal of Ecology and Life Safety)
The methods of the quality increase of the air-water mixture generated by ejection system of aeration for the flotation wastewater treatment are considered such as the use of various constructions of ejectors, use of dispersers, operating at different air-water rates and exit nozzle velocities, addition of surfactants. It is shown that for the highly efficient wastewater treatment microbubbles with the sizes less than 100 µm that are equally distributed in the flotation chamber are needed. The use of aeration system that includes ejector, aerator and disperser is offered. The experimental definition of air-water mixture characteristics (bubbles size and superficial gas velocity) was carried out with different exit nozzle velocities and types of aerators. The operating mode that allows the generation microbubbles with average sizes 75-115 µm was defined. At this mode the annular aerator with inside diameter 4 mm and outside diameter 6 mm was used, exit nozzle velocity was 13 m/s.